Slowacki’s Chopin - Seweryn, Agata (Interdisciplinary Studies in Musicology, 2018)
Supposed analogies between Fryderyk Chopin and Juliusz Słowacki form a recurring thread that runs through the subject literature o f Romantic culture. Legions of literati, critics, literary scholars and musicologists have either attempted to find affinities between Chopin and Słowacki (on the level of both biography and creative output) or else have energetically demonstrated the groundlessness of all analogies, opinions and assumptions. Consequently, stereotypes have been formed and then strengthened concerning the relations between the two creative artists, particularly the conviction of Slowacki’s dislike of Chopin and his music, which - in the opinion of many scholars - the poet simply did not understand. Considerations of this kind most often centre on a famous letter written by Słowacki to his mother in February 1845. However, a careful reading of this letter and its comparison with Slowacki’s other utterances on the subject of Chopin shows that opinions of the poet’s alleged insanity, petty-mindedness or lack of subtlety in his contacts with Chopin’s music are most unjust. The analysed letter is not so much anti-Chopin as anti-Romantic. It inscribes itself perfectly in the context of the thinking of “the Słowacki of the last years”, since the poet negates crucial aesthetic features o f Romantic music, but at the same time criticises his own works: W Szwajcarii [In Switzerland] and, in other letters, Godzina myśli [An hour of thought] and the “picture of the age”, the poetical novel Lambro. It also turns out that what Słowacki says about the polonaises tallies with the opinions of musicologists and musicians writing about “late Chopin”.